2015
DOI: 10.1182/blood-2014-06-585273
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a maintains mouse hematopoietic stem cell self-renewal by regulating Dnmt3a

Abstract: • miR-29a maintains HSC function by targeting Dnmt3a.Hematopoietic stem cells (HSCs) possess the ability to generate all hematopoietic cell types and to self-renew over long periods, but the mechanisms that regulate their unique properties are incompletely understood. Herein, we show that homozygous deletion of the miR-29a/b-1 bicistron results in decreased numbers of hematopoietic stem and progenitor cells (HSPCs), decreased HSC self-renewal, and increased HSC cell cycling and apoptosis. The HSPC phenotype is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 47 publications
2
52
1
Order By: Relevance
“…In addition, the functional importance of both Dnmt3a and miR-29a for Wif1 gene methylation and Wif1 expression as well as for CPC differentiation was verified in naive CPCs in monocultures as well as in the coculture model, respectively. Our identification of the miR-29 family based on bioinformatic analysis corroborates previous reports on Dnmt3a regulation by miR-29a in other cell types (27,28) and is supported by our expression as well as miR-29a mimic and inhibition data. Altogether, we demonstrated that miR-29a indirectly modifies the methylation pattern of the Wif1 gene, promoting its expression through Dnmt3a downregulation, which is also key for the effect of miR-29a on differentiation.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the functional importance of both Dnmt3a and miR-29a for Wif1 gene methylation and Wif1 expression as well as for CPC differentiation was verified in naive CPCs in monocultures as well as in the coculture model, respectively. Our identification of the miR-29 family based on bioinformatic analysis corroborates previous reports on Dnmt3a regulation by miR-29a in other cell types (27,28) and is supported by our expression as well as miR-29a mimic and inhibition data. Altogether, we demonstrated that miR-29a indirectly modifies the methylation pattern of the Wif1 gene, promoting its expression through Dnmt3a downregulation, which is also key for the effect of miR-29a on differentiation.…”
Section: Discussionsupporting
confidence: 79%
“…Their work also suggested that Dnmt3a may be a target gene of miR-29, thus contributing to the phenotype of miR-29a/b-1-null HSPCs through negative regulation [93]. What is more, other microRNAs can work through different ways, such as miR-33 can control HSCs selfrenewal by mediating the down-regulation of p53 [94], and miR-126 can arrest cell cycle progression of HSC in vitro and in vivo by PI3 K/AKT/GSK3 pathway, increasing HSC proliferation without inducing exhaustion [95,96].…”
Section: Other Non-classical Regulators For Hsc Cell Cycle Micrornasmentioning
confidence: 97%
“…No defects in HSC [89] MicroRNAs miR-29a Enhanced proliferation of HSPC [92,93] miR-33 Enhanced HSCs self-renewal [94] miR-126 Decreased HSC proliferation [95,96] numbers of HSPCs, decreased HSC self-renewal, and increased HSC cell cycling and apoptosis using homozygous deletion of the miR-29a/b-1, mainly due to loss of miR-29a. Their work also suggested that Dnmt3a may be a target gene of miR-29, thus contributing to the phenotype of miR-29a/b-1-null HSPCs through negative regulation [93].…”
Section: Other Non-classical Regulators For Hsc Cell Cycle Micrornasmentioning
confidence: 99%
“…MicroRNAs are also expressed in a lineage-specific fashion and have been shown to play key roles in the regulation of hematopoiesis. [2][3][4] Other sncRNAs include small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs), small interfering RNAs, and Piwi-interacting RNAs. With some exceptions, the expression of these other sncRNAs in hematopoietic cells and their contribution to the regulation of hematopoiesis are not well characterized.…”
Section: Introductionmentioning
confidence: 99%